Clinical and immunological characteristics of Aspergillus fumigatus-sensitized asthma and allergic bronchopulmonary aspergillosis - Chen, Hao; Zhang, Xinyu; Zhu, Li; An, Nairui; Jiang, Qing; Yang, Yaqi; Ma, Dongxia; Yang, Lin; Zhu, Rongfei (Frontiers in Immunology, 2022)
Background Aspergillus fumigatus (A.f) is a common airborne allergen that contributes to allergic asthma. In some patients, A.f can colonize in the airway and lead to allergic bronchopulmonary aspergillosis (ABPA). However, our understanding of the pathogenesis of A.f-sensitized asthma and ABPA remains inadequate. Objective We aimed to investigate the clinical and immunological characteristics of A.f-sensitized asthma and ABPA. Methods A total of 64 ABPA and 57 A.f-sensitized asthma patients were enrolled in the study, and 33 non-A.f-sensitized asthma patients served as the control group. The clinical and immunological parameters included lung function, fractional exhaled nitric oxide (FeNO), induced sputum and blood cell analysis, specific IgE/IgG/IgA of A.f and its components, cytokines (IL-33, IL-25, and TSLP) and CD4+T cell subsets. Results The eosinophils in blood, induced sputum, and FeNO were significantly higher in ABPA patients compared to that in A.f-sensitized patients. The combination of FeNO and eosinophils (EO) parameters presented good diagnostic efficiency in differentiating A.f (+) asthma from ABPA, with a sensitivity of 80% and a specificity of 100%. Specific IgE, IgG, and IgA against A.f also increased in ABPA patients. However, serum IL-25, IL-33, and TSLP showed no significant differences between the two groups. Cell analysis showed an increase in IFN-γ+Th1 cells in the ABPA patients. FlowSOM analysis further confirmed that the frequency of CD3+CD4+PD-1+CD127+IFN-γ+T cells was higher in ABPA patients. Conclusion Our findings suggest the distinct humoral and cell immunological responses in A.f-sensitized asthma and ABPA patients. ABPA patients have more severe eosinophilic inflammation and enhanced Th1 responses compared with A.f-sensitized asthma patients.